Gastroscopy assisted laser Doppler flowmetry and visible light spectroscopy in patients with chronic mesenteric ischemia. (3rd October 2019) - Berge, Simen T.; Safi, Nathkai; Medhus, Asle W.; Ånonsen, Kim; Sundhagen, Jon O.; Hisdal, Jonny; Kazmi, Syed S. H
Abstract: Mucosal pathology due to chronic mesenteric ischemia (CMI) is rarely seen during upper endoscopy. Combining Laser Doppler Flowmetry (LDF) and Visible Light Spectroscopy (VLS) may aid in detection of CMI at an early stage. We aimed to investigate the utility of LDF and VLS in detecting microcirculatory changes in patients with CMI during upper endoscopy. In a single center, prospective study, 104 patients were evaluated for mesenteric ischemia during a 24 months period. Patients with a consensus diagnosis of CMI ( n  = 40) were examined with LDF and VLS. Thirty-two were successfully treated and had a definitive diagnosis of CMI. Results were compared with controls ( n  = 38) with normal intestinal circulation evaluated with duplex ultrasonography (DUS). Treatment response was evaluated clinically and with DUS at 1 month and with VLS and LDF at 3 months. A significant reduction in mucosal capillary hemoglobin oxygen saturation (SO2 ) was found in CMI patients compared to controls before treatment: mean ± SD: 67 ± 9%, 81 ± 4%, respectively ( p  < .001). A significant reduction was also seen for the relative hemoglobin (rHb) amount, flow and velocity ( p  < .001). The sensitivity of SO2 measured by VLS for diagnosing CMI was 94% and the specificity 72% (cut-off 78%), calculated with ROC curve analysis. A combination of SO2 and rHb increased the test sensitivity and specificity to 97% and 79%, respectively. Conclusion: CMI patients have significantly reduced microcirculation in the stomach and duodenum compared to controls. The results suggest that VLS should be included when performing an upper endoscopy in patients with suspected CMI.